Breakfast Quality and Menu Variety as Predictors of Guest Satisfaction at Pangeran Beach Hotel Padang - Deki Hariyanto (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
The abstract should be informative and provide a clear statement of the problem, proposed approach or solution, and indicate the main findings and conclusions. Abstract should be 150 to 200 words long. Abstracts must be written in the past tense and use English and Indonesian based on their placement in the abstract table provided. Abstract and keywords are written in Cambrian (10 pt) format. There is no literature to be cited. The keyword list provides the opportunity to add keywords, which are used by indexing services. Consists of 3 to 5 keywords. The use of keywords should make it easier for interested parties to find your article. We recommend that you download this journal template to make it easier to adjust your writing before submitting an article. Breakfast is a salient hotel service encounter in that it influences the guests’ evaluations early in the day and combines product quality, operational readiness and menu choice. The objective of this research was to find out breakfast quality and menu variety as predictor of guest satisfactions at Pangeran Beach Hotel, Padang. An explanatory cross sectional survey was conducted on 105 guests selected by purposive sampling. The respondents had to be at least 18 years old and had to have stayed at least two nights and used the breakfast service at least twice. Data were collected using 30 items five point Likert questionnaire and were analyzed using multiple linear regression. All items were above the corrected item-total correlation threshold of 0.30. Construct reliability ranged from 0.817 to 0.825. The quality of breakfast was a positive predictor of guest satisfaction (B = 0.365; beta = 0.374; t = 4.266; p < 0.001), as was menu variety (B = 0.272; beta = 0.275; t = 3.135; p = 0.002). The full model was significant, F(2,102) = 18.529; p < 0.001, and accounted for 26.6% of the variance in satisfaction. Somewhat more powerful predictor was the quality of the breakfast. The results suggest the need for integrated controls for taste, freshness, temperature, hygiene and refill speed, and systematic menu rotation based on guest preferences.